Reading Heresy Religion and Dissent in Literature and Art. - Erickson, Gregory; Schweizer, Bernard (Berlin/Boston : De Gruyter, 2017)
Heresy studies is a new interdisciplinary, supra-religious, and humanist field of study that focuses on borderlands of dogma, probes the intersections between orthodoxy and heterodoxy, and explores the realms of dissent in religion, art, and literature. Free from confessional agendas and tolerant of both religious and non-religious perspectives, heresy studies fulfill an important gap in scholarly inquiry and artistic production. Divided into four parts, the volume explores intersections between heresy and modern literature, it discusses intricacies of medieval heresies, it analyzes issues of heresy in contemporary theology, and it demonstrates how heresy operates in artistic and literature creativity today. Rather than treating matters of heresy, blasphemy, unbelief, dissent, and non-conformism as subjects to be shunned or naively championed, the essays in this collection chart a middle course, energized by the dynamics of heterodoxy, dissent, and provocation, yet shining a critical light on both the challenges and the revelations of disruptive kinds of thinking and acting.
Frontmatter -- Table of Contents -- Preface / Schweizer, Bernard -- Introduction / Erickson, Gregory / Schweizer, Bernard -- I. Heresy and Modern Literature -- Heresy and the Modernist Imagination / Erickson, Gregory -- "No, I better not say it. I might get punished": Misotheism and Self-Creation in Tomás Rivera's ... And the Earth Did Not Devour Him / Hama, Mark -- The Absolute Heterodoxy of William Blake / Altizer, Thomas J. J. -- II. Medieval Heresy -- Unbelief and the Problem of Heresy: A Late Medieval Context / Calder, Natalie -- The Joys of Heresy: Benefits for Women in Medieval Heretical Sects / Green, Kathryn -- III. Heretical Theology -- Saint Augustine: The Neoplatonic Father of Heretical Orthodoxy / Holloway, John Daniel -- Making the World: Against Spirituality / Miller, Jordan E. -- The Heresy of Humor: Theological Responses to Laughter / Schweizer, Bernard -- IV. From the Creators: The Artists' Corner -- The Novelist as Heretic / Morrow, James -- Beautiful Heresy: A Visual Artist's Re-appropriation of Scripture / Hannon, Susan -- Pop Heresy: Songwriting at the Edge of the Speakable / Golden, Tasha -- Adapting Candide for the Stage / Wood, Stanton -- Epilogue: Heretical Unmaking / Erickson, Gregory -- Notes on the Contributors -- Index
Description based upon print version of record.
Added to collection customer.56279.3 - Master record variable field(s) change: 072
Keywords: Blasphemie; Blasphemy; Dissens; Dissent; Heresy; Ketzerei; Non-Conformism.; Blasphemy; Dissensi; PHILOSOPHY / Ethics & Moral Philosophy; Electronic books